The Computer Modeling of Aircraft Recognition by the Onboard Radiating Signal Features Based on the Similarity Indices Calculation Algorithm - Kaliuzhnyi, M.; Kolisnyk, V.; Khriapkin, O.; Nikolayev, I. (IEEE, 2020)
This paper consists of a methodical approach to solve the problem of aircraft recognition by the radiation features of airborne radar stations and radio communications based on the application of the similarity indices calculation algorithm. The results of the efficiency estimation by the similarity Indices calculation algorithm for the radiation objects recognition with different signal features combinations are presented. Computer simulation and statistical modeling are carried out and some results are given here. The paper says the similarity indices calculation algorithm can provide a high recognition probability a lot of radiation aircraft classes with the optimal rule for calculating objects similarity in a selected space of signal features.
Keywords: airborne radar station; radiation signal features; recognition; radiation aircraft; similarity indices calculation algorithm